Afro-Brazilian Visual Arts in Education: A Black Perspective for Teaching Arts in Early Childhood - Lima, Ivan; Ramos, Shirley Silva (Farol, 2025)
This article discusses the potential of Afro-Brazilian visual arts in early childhood arts education. Based on bibliographic research, the article seeks to understand educational legislation on African and Afro-Brazilian history and culture in education. The article concludes that it is relevant as a contribution to educators, who can bring African-based arts into basic education, expanding the concept of identity and representation of Black people in Brazil.
Keywords: art education; afro-brazilian visual arts; early years; education